A study on objective evaluation of vehicle steering comfort based on driver's electromyogram and movement trajectory - Liu, Yahui; Liu, Qi; Lv, Chen; Zheng, Minghui; Ji, Xuewu (IEEE, 2017)
The evaluation of driver's steering comfort, which is mainly concerned with the haptic driver–vehicle interaction, is important for the optimization of advanced driver assistance systems. The current approaches to investigating steering comfort are mainly based on the driver's subjective evaluation, which is time-consuming, expensive, and easily influenced by individual variations. This paper makes some tentative investigation of objective evaluation, which is based on the electromyogram (EMG) and movement trajectory of the driver's upper limbs during steering maneuvers. First, a steering experiment with 21 subjects is conducted, and EMG and movement trajectories of the driver's upper limbs are measured, together with their subjective evaluation of steering comfort. Second, five evaluation indices including EMG and movement information are defined based on the measurements from the first step. Correlation analyses are conducted between each evaluation index and steering comfort rating (SCR), and the results show that all of the indices have significant correlations with SCR. Then, an artificial neural network model is devised based on the aforementioned indices and its predicting performance of SCR is demonstrated as acceptable. The results reveal that it may be feasible to establish an objective evaluation approach for vehicle steering comfort.
Keywords: Vehicles; Electromyography; Muscles; Trajectory; Vehicle dynamics; Predictive models; EMG; Haptic driver-vehicle interaction; Movement trajectory; Objective evaluation; Steering comfort